2020
DOI: 10.1016/j.jns.2020.117054
|View full text |Cite
|
Sign up to set email alerts
|

Time to diagnosis and factors affecting diagnostic delay in amyotrophic lateral sclerosis

Abstract: Amyotrophic lateral sclerosis (ALS) is a progressive, degenerative neuromuscular disease with limited treatment options. The diagnosis of ALS can be challenging for numerous reasons, resulting in delays that may compromise optimal management and enrollment into clinical trials. Several studies have examined the process and challenges regarding the clinical diagnosis of ALS. Twenty-one studies that were almost exclusively from the English literature published between 1990 and 2020 were identified via PubMed usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
78
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 103 publications
(82 citation statements)
references
References 47 publications
4
78
0
Order By: Relevance
“…The recent literature review (10) found that the typical delay to diagnosis for ALS patients is 10-16 months reviewed studies from 1990 to 2020, which suggests the establishment of clinical diagnostic criteria and growing public awareness of ALS may not have been sufficient to significantly shorten delay (20). While this chapter has addressed the "what" and the "where" with regard to ALS diagnostic delay, there remains the question of why?…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The recent literature review (10) found that the typical delay to diagnosis for ALS patients is 10-16 months reviewed studies from 1990 to 2020, which suggests the establishment of clinical diagnostic criteria and growing public awareness of ALS may not have been sufficient to significantly shorten delay (20). While this chapter has addressed the "what" and the "where" with regard to ALS diagnostic delay, there remains the question of why?…”
Section: Discussionmentioning
confidence: 99%
“…The study reporting the longest delay of 2.25 years, as mentioned in the review paper by Richards et al (10), showed a substantial difference between delays in the bulbar-onset group (1.25 years) compared to the spine-onset group (2.5 years) (18). Of note, for patients presenting with both bulbar and spine symptoms, the median time to diagnosis dropped to 0.25 years (10,18). Patients with spinal-onset presentation also receive more differential diagnoses than those with bulbar presentation (26) and are more likely to be misdiagnosed (27).…”
Section: Disease Phenotype and Diagnostic Delaymentioning
confidence: 99%
See 1 more Smart Citation
“…Progression of the disease in patients is considered to be one of the causes of clinical trial failure, because motor neurons start to disappear, and the urgency for diagnosis is increasingly emphasized. Attempts to create new diagnostic criteria 22 and the development of biomarkers 23,24 are promising, but they have as yet not predicted ALS diagnosis 25 . Thus, by combining our model, which is expected to be a supportive tool for ALS diagnosis, and clinical biomarkers including blood/spinal fluid neurofilament levels, it may be possible to classify ALS with even greater accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…Current diagnosis is based on clinical examination (El-Escorial criteria) [3] and neurophysiological examination (Awaji criteria) [4], while recently the ALS diagnostic index was also described [5]. Despite all this, establishing the correct diagnosis can still take one year or more [6]. Therefore, reliable and easy-to-obtain biomarkers are in desperate need for earlier and more accurate diagnoses.…”
Section: Introductionmentioning
confidence: 99%